Effects of capecitabine as part of neo-/adjuvant chemotherapy – A meta-analysis of individual breast cancer patient data from 13 randomised trials including 15, 993 patients. (May 2022) - van Mackelenbergh, Marion T.; Seither, Fenja; Möbus, Volker; O'Shaughnessy, Joyce; Martin, Miguel; Joensuu, Heikki; Untch, Michael; Nitz, Ulrike; Steger, Guenther G.; Miralles, Juan J.; Barrios, Carlos H.; Toi, Masakazu; et al.
Abstract: Background: Despite the large number of patients with early breast cancer (EBC) who have been treated with capecitabine in randomised trials, no individual patient data meta-analysis has been conducted. The primary objective was to examine the effect of capecitabine on disease-free survival (DFS), and the secondary objectives were to analyse distant DFS (DDFS), overall survival (OS), pathological complete response (for neoadjuvant studies) and the interaction between capecitabine-related toxicity and treatment effect. Methods: www.clinicaltrials.gov and www.pubmed.ncbi.nlm.nih.gov were searched using the following criteria: use of capecitabine for EBC as adjuvant or neoadjuvant therapy; multicentre randomised trial with >100 patients; recruitment completed, and outcomes available. Required data were available for 13 trials. Results: Individual data from 15, 993 patients were collected. Cox regression analyses of all included patients revealed that the addition of capecitabine did not alter DFS significantly compared with treatment without capecitabine (hazard ratio [HR] 0.952; 95% CI 0.895–1.012; P value = 0.115). There was also no effect on DFS in the subset of studies where capecitabine was given instead of another drug (HR 1.035; 95% CI 0.945–1.134; P  = 0.455). However, capecitabine administered in addition to the standard systemic treatment improved DFS (HR 0.888; 95% CI 0.817–0.965; P  = 0.005). An OS improvement was observed in the entire cohort (HR 0.892; 95% CI 0.824–0.965, P  = 0.005) and in the subset of capecitabine addition (HR 0.837; 95% CI 0.751, 0.933, P  = 0.001). Subgroup analyses revealed that triple-negative breast cancer (TNBC) patients benefitted from treatment with capecitabine overall and in addition to other systemic treatments in terms of DFS and OS. Conclusion: Capecitabine was able to improve DFS and OS in patients with TNBC and in all patients with EBC when administered in addition to systemic treatment. Highlights: Capecitabine improved disease-free survival (DFS) when administered in addition in early breast cancer. Overall survival (OS) was improved by capecitabine treatment in the overall cohort. Triple-negative breast cancer patients benefitted from capecitabine overall and as add on regarding DFS and OS. Patients with high-grade tumours benefitted from capecitabine.